Diskualifikasi Pasangan Calon Bupati dan Wakil Bupati Bangkalan Madura Perspektif Fikih SiyÃ¢sah - Rahmat, Rahmat (Prodi Siyasah Jinayah (Hukum Tata Negara dan Hukum Pidana Islam) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2015)
Abstract: This article discusses about the disqualification of the candidate of regent and vice regent in Bangkalan-Madura within the Islamic political jurisprudence perspective. In a decision No. 136/G/2012/PTUN.Sby, the Surabaya State Administrative Court decided that regent and vice regent in Bangkalan-Madura, which is signed by the leader of the National Unity Party (PPN), is legally flawed on the basis of article 1, paragraph 12, article 57 paragraph 3 of Regulation of KPU No. 6 year 2011. The decision is by the consideration that the National Unity Party is not a new party. It is just changing the name of the Regional Unity Party that should remain as chairman and secretary of the DPC PPN of Bangkalan-Madura. The judge of the Surabaya State Administrative Court within his legal decision No. 136/G/2012/PTUN.Sby set the proposal of the regent and vice regent in Bangkalan-Madura.Keywords: Disqualification, candidates, regent, Islamic jurisprudence.